Pneumocystis jirovecii Diversity in Réunion, an Overseas French Island in Indian Ocean - Le Gal, Solène; Hoarau, Gautier; Bertolotti, Antoine; Negri, Steven; Le Nan, Nathan; Bouchara, Jean-Philippe; Papon, Nicolas; Blanchet, Denis; Demar, Magalie; Nevez, Gilles (Frontiers in Microbiology, 2020)
Data on P. jirovecii characteristics from the overseas French territories are still scarce whereas numerous data on P. jirovecii genotypes are available for metropolitan France. The main objective of the present study was to identify P. jirovecii multilocus genotypes in patients living in Réunion and to compare them with those identified using the same method in metropolitan France and in French Guiana. Archival P. jirovecii specimens from immunosuppressed patients, 16 living in Réunion (a French island of the Indian ocean), 6 living in French Guiana (a South-American French territory), and 24 living in Brest (Brittany, metropolitan France) were examined at the large subunit rRNA (mtLSUrRNA) genes, cytochrome b (CYB), and superoxide dismutase (SOD) genes using PCR assays and direct sequencing. A total of 23 multi-locus genotypes (MLG) were identified combining mtLSUrRNA, CYB and SOD alleles, i.e. six in Reunionese patients, three in Guianese patients, and 15 in Brest patients. Only one MLG (mtLSU1-CYB1-SOD2) was shared by Reunionese and Guianese patients (one patient from each region) whereas none of the 22 remaining MLG were shared by the 3 patient groups. A total of eight MLG were newly identified, three in Réunion and five in Brest. These results that were obtained through a retrospective investigation of a relatively low number of P. jirovecii specimens, provides original and first data on genetic diversity of P. jirovecii in Réunion island. The results suggest that P. jirovecii organisms from Réunion present specific characteristics compared to other P. jirovecii organisms from metropolitan France and French Guiana.